Where Credit is due: on the Puerto Rican Debt Crisis - Joshi, Eric; Joshi, Amogh (Information Management and Business Review, 2017)
This paper provides a comprehensive breakdown of the ongoing economic crisis in the Commonwealth of Puerto Rico. It explores the backdrop of the crisis by analyzing Puerto Rico’s relationship with the U.S., macroeconomic indicators and pertinent legislations. It’s entirely unique contribution is the analysis of the newly introduced act- PROMESA, which enables Puerto Rico to restructure its debt. We have provided an explanation of the important sections of this legislation which govern the debt negotiation process. The PROMESA act has been extended to apply to other unincorporated territories of the United States as well should they run into arrears, which broadens the scope of this paper. We have extended the findings of pre-existing body of work on sovereign debt restructuring hurdles and explained how PROMESA addresses them. We have also used previous works to suggest measures to expedite Puerto Rico’s debt restructuring process with creditors. This paper could also serve as a handbook for creditors looking to navigate through the post-PROMESA debt restructuring process.